Et de lupis grex fecundus multiplicatur agnorum. Le paysage ecclésiastique de la Byzacène méridionale et de la Tripolitaine occidentale - Ellefi, Mohamed (Libyan Studies, 2024)
This article reflects on aspects of the ecclesiastical landscape in southern Byzacena and western Tripolitania. The aim is to highlight the conditions of creation and the process of evolution of the ecclesiastical landscape in a territory with a particular geographical identity. In this context, the approach is based on three clearly defined conditions: first, the factors favourable to the appearance and then the development of Christianity in this space; secondly that its main episcopal seats were divided into three essential sets –the bishoprics of the ecclesiastical district called by late sources Arzugitana,the seats of the Gafsa region, and those of the coastal plains of Aradh and Jfara; finally, the particularities of the ecclesiastical landscape with its imprecise boundaries between ecclesiastical and administrative subdivisions and the low representation of Tripolitania in African councils and religious tolerance., ومن الذئاب يتكاثر قطيع الحملان الخصيب. المشهد الكنسي لجنوب بيزاسينا.محمد اللافييقدم هذا المقال ملاحظات عن جوانب المشهد الكنسي في جنوب بيزاسينا و غرب إقليم تريبوليتانيا. ويفحص الوثائق الكنسية بما في ذلك وقائع مؤتمرات قرطاج التي عقدت في 411 و 419، وقصص القديس أوغسطين وفيكتور دي فيتا والبيانات من وثيقة نوتيتسيا (Notitia) 484 . نحن نهدف هنا إلى تسليط الضوء على ظروف تكون وعملية تطور المشهد الكنسي في منطقة ذات هوية جغرافية معينة. حيث تطل على غرب إقليم تريبوليتانيا وجنوب بيزاسينا. وفي هذا السياق، اتبعنا منهجاً يقوم على ثلاثة محاور محددة بوضوح. أولاً، العوامل المواتية لظهور المسيحية ثم تطورها في هذا الفضاء. ثم تم تقسيمها إلى ثلاث مجموعات أساسية. من ناحية، أساقفة المنطقة الكنسية التي تسمى حسب المصادر المتأخرة أرزوجيتانا. ومن جهة أخرى مقاعد منطقة قفصة ومقاعد السهول الساحلية عرادة و الجفارة. أخيراً يتم التركيز على مشكلتين مرتبطتين بالمشهد الكنسي في جنوب بيزاسينا. تتعلق بعدم دقة حدود التقسيمات الكنسية في بيزاسينا و إقليم تريبوليتانيا وانخفاض تمثيل تريبوليتانيا في المجالس الأفريقية.
Keywords: Antiquité; Donatisme

العملة والسلطة بأفريكا فيما بين الفترة الرومانيّة والونداليّة - الحاج نصر لوم, زكية (2024)
Keywords: Antiquité

L’hydraulique urbaine de Gigthi et de Meninx - Drine, Ali (L’eau agent de paysages et facteur de risques, 2024)
Keywords: Antiquité

Les Murileguli de Meninx - Drine, Ali (L'Africa antica dall'eta repubblicana ai Giulio-Claudii: l'Africa Romana, XXII, 2024)
Meeting Name: L' Africa romana
Keywords: Antiquité